Diagnóstico prenatal de anomalías congénitas en la era de la cirugía fetal en México - Cruz-Martínez , Rogelio (Mexican Journal of Medical Research ICSA, 2020)
The clinical utility of fetal ultrasound in the prenatal diagnosis of different congenital anomalies has been advancing towards better accuracy in recent years, mainly due to technological improvements in current ultrasound devices, and incorporation of formal programs for fetal ultrasound training by different international and national societies worldwide. A proportion of congenital malformations suitable for prenatal diagnosis, at risk of either intrauterine fetal demise or neonatal death if left untreated, have now the possibility to benefit fromfetal surgery in order to improve prognosis, leading to mandatory accurate prenatal diagnosis and timely referral to a fetal surgery center. However, despite fetal intervention, a higher neonatal mortality might be expected in fetuses with congenitalanomalies managed in countries like ours where termination of pregnancy is not allowed, suboptimal neonatal management due to limited neonatal intensive care unit capabilities, and the influence by social and economic factors.